The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1530/rep-15-0010
|View full text |Cite
|
Sign up to set email alerts
|

Placental changes caused by food restriction during early pregnancy in mice are reversible

Abstract: In a previous study, 50% calorie restriction in mice from d1.5 to 11.5 of pregnancy resulted in reduced placental weights and areas, relativel sparing of labyrinth zone area compared to junctional zone area, and dramatic changes in global gene expression profiles. However, little lasting effect was seen on adult offspring of these pregnancies, with a slight reduction in adiposity in males and some changes in liver gene expression in both sexes. The goals of the present study were to determine whether the place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 45 publications
2
12
0
Order By: Relevance
“…Previous studies in mice reported similar temporal-specific response in fetal growth. Calorie restriction by 50% during E1.5–11.5 led to placental weight reduction in early gestation, yet this weight reduction was reversed at E18.5 51 , 52 . Over-nutrition induced by a high-sugar, HF diet reduced feto-placental growth at E16, yet fetal weight was normalized at E19 53 .…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies in mice reported similar temporal-specific response in fetal growth. Calorie restriction by 50% during E1.5–11.5 led to placental weight reduction in early gestation, yet this weight reduction was reversed at E18.5 51 , 52 . Over-nutrition induced by a high-sugar, HF diet reduced feto-placental growth at E16, yet fetal weight was normalized at E19 53 .…”
Section: Discussionmentioning
confidence: 97%
“…There may also be catch-up growth of the placenta in late gestation if the nutritionally-deprived dams are returned to ad libitum feeding of the control diet. For instance, the effect of global undernutrition to reduce placental weight was mitigated by ad libitum feeding of the dam in late pregnant mice (Harper et al, 2015 ). This suggests alterations in the placenta caused by nutrient restriction in early pregnancy could be reversible.…”
Section: Regulation Of Fetal and Placental Weights By The Maternal Enmentioning
confidence: 99%
“…One utilizes vascular corrosion casts of placental fetal vessels that are scanned by x-ray microcomputed tomography and quantified (Rennie et al, 2015). The other method utilizes a quantitative morphometric approach in which maternal vs. fetal sinuses in the placental labyrinth are manually traced (identified by the presence vs. the absence of red blood cells, respectively), pseudo-colored, and quantified with Image J (Harper et al, 2015; Li et al, 2013; Schulz et al, 2012; Van Gronigen Caesar et al, 2016). We chose the latter method for this study because it afforded us the ability to quantitatively analyze potential changes in both the fetal and the maternal sinuses of the labyrinth.…”
Section: Resultsmentioning
confidence: 99%